2003
DOI: 10.1007/bf02256434
|View full text |Cite
|
Sign up to set email alerts
|

A p53 codon 72 polymorphism associated with prostate cancer development and progression in Japanese

Abstract: An association between the Pro/Pro genotype of p53 codon 72 and a lower risk of prostate cancer in Caucasians was recently reported. However, the association of this polymorphism with prostate cancer risk in a Japanese population has not been clarified. We performed a case-control study consisting of 114 prostate cancer patients and 105 noncancer controls. Sixty-nine percent (79 of 114) of the patients had a positive family history. The genotypic frequencies in the controls were 39.0% for Arg/Arg, 54.3% for Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 22 publications
1
43
1
1
Order By: Relevance
“…Furthermore, the Arg/Arg genotype and reduced cancer risk has also been reported (34). A study performed in a Japanese population revealed that the Pro/Pro genotype at codon 72 was associated with increased risk of prostate cancer and its progression (35). Two separate meta-analyses by Jia et al (36) and Lao et al (37) suggested that the homozygote and heterozygote genotypes of Pro participated in the development of endometriosis in Asian and Caucasian populations.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the Arg/Arg genotype and reduced cancer risk has also been reported (34). A study performed in a Japanese population revealed that the Pro/Pro genotype at codon 72 was associated with increased risk of prostate cancer and its progression (35). Two separate meta-analyses by Jia et al (36) and Lao et al (37) suggested that the homozygote and heterozygote genotypes of Pro participated in the development of endometriosis in Asian and Caucasian populations.…”
Section: Discussionmentioning
confidence: 89%
“…In other studies, however, authors have found the opposite correlation, instead demonstrating an association between the P72 (lesser apoptotic) variant and increased risk for other cancer types, including cancer of the thyroid (Granja et al, 2004), nasopharynx (Tsai et al, 2002a, b;Tiwawech et al, 2003), prostate (Suzuki et al, 2003), skin (Chen et al, 2003), urogenital region (Kuroda et al, 2003), and lung Fan et al, 2000;Zhang et al, 2003). Still other groups have failed to demonstrate any association between codon 72 variants of p53 and cancer risk.…”
Section: The Codon 72 Polymorphismmentioning
confidence: 95%
“…Based on genomewide scans, such susceptibility loci and genetic alterations were attributed to chromosomes, 1,7,8,10,12,17,18,20, X, and the Y chromosome. [9][10][11][12][13][14] A large amount of data has been generated about alterations, aberrations, rearrangements, gain, or loss of Y-chromosome materials in prostate cancer using different techniques of molecular cytogenetics. [15][16][17][18][19][20] The simple fact that the Y chromosome and prostate cancer have male-specificity in common lead many researchers to investigate if there is Y involvement in such a male-specific cancer, however, yet there is no clear conclusions.…”
Section: Introductionmentioning
confidence: 99%